Crisis of the Age of Maturity, The Formation of The Image of “I” - Yuldoshev Tojiddin Abdukarimovich; Karakulov Abdunazar Nurmamatovich; Sharafullayeva Shakhlo Kakhramonovna (Global Scientific Publishing, 2022)
A person's self - awareness, knowledge and work on himself requires that first of all his attention, consciousness is directly focused on himself, on his own inner capabilities, abilities, emotional experiences. That is, social behavior requires the Coordination of roles by the individual, through the systematic analysis of their personal actions, their consequences, in addition to paying attention to their behavior, the people who surround him. In this article, opinions and reflections are made on the crisis of the age of maturity and the formation of the image of me in their inner world.
Keywords: period of maturity; youth; psychology; mental and physiological development